Coordination polymeric fluorescent gel: effect of removal of branch substituents of the central core over properties. Issue 9 (3rd May 2019) - Pandey, Vinay Kumar; Singh, Vikas Kumar; Chandra, Subhash; Hasan, Syed Hadi
Abstract: A fluorescent gel has been prepared by deprotonation of non-fluorescent adipic acid derived ligand (H4 AL) with LiOH followed by coordination with Cd(II) in DMF. The mechanism of gelation is examined by IR, 1 H NMR, UV-vis, Job's plot, PXRD, SEM and TEM. Chelation enhanced fluorescence by Cd(II) has been established by fluorescence experiments. In addition to synthesis and characterization of this gel, we compared the gel properties by varying the core of the ligand using citric (H6 CL) acid derivatives. Abstract :